Exploring Exceptions to the Sulfonate-Mediated Dehydrative Glycosylation Using L-Digitoxose as a Model - Chan, Keith Chi-Ki (Tufts Archival Research Center, 2023)
The Bennett lab’s glycosylation methodology usually produces β-selective linkages. However, more recent works have suggested that if the substituent of the donor at C3 switches from an equatorial position to axial, the same glycosylation conditions favor the opposite α-selectivity. In this thesis, I hypothesize that the axial C3-substituents are directly responsible for the observed α-selectivity, and I shall test this with L-digitoxose as a model. Preliminary glycosylations with different protecting groups at the C3 position indicated dropping selectivity going from 2-naphthylmethyl to benzyl to methyl.; Thesis (B.S.)--Tufts University, 2023.; Submitted to the Dept. of Chemistry.; Advisor: Clay S. Bennett.; Committee: Sam Thomas, Krishna Kumar.